MATH 101 HOMEWORK 1 – SOLUTIONS √ √ 1. First of all, for the limit to be finite we must have lim ax + b − 4 = 0, ie. b = 4, x→0 b = 16. Also, from l’Hopital’s rule we have √ ax + 16 − 4 = lim lim x→0 x→0 x So we must have a/8 = 1, ie. a = 8. √ 1 2 ax+16 1 ·a a a = √ = . 8 2 16 2. (a) At (t, t2 ), the tangent has slope y 0 = 2t, hence the equation of the tangent is y − t2 = 2t(x − t). Rewrite this as y = 2tx − t2 and set m = 2t, then the equation becomes y = mx − m2 /4 as required. (b) The slope of the tangent at x = t is y 0 = 2at + b, so the equation of the tangent is y − (at2 + bt + c) = (2at + b)(x − t), which simplifies to y = (2at + b)x − at2 + c. Let m = 2at + b, then t = (m − b)/2a, so that m−b 2 (m − b)2 f (m) = −at2 + c = −a( ) +c− + c. 2a 4a 3. (a) Let |AB| = x, |AC| = y, |AD| = d, where AD is the bisector. The area of the triangle ABC is √ 1 xy 3 ◦ xy sin(120 ) = . 2 4 This area is also equal to the sum of areas of the triangles ABD and ADC, which is √ 1 3 1 ◦ ◦ xd sin(60 ) + yd sin(60 ) = (x + y)d. 2 2 4 This gives us an equation for d: xy = (x + y)d. We solve it and plug in xy = 1: 1 1 x xy = = = 2 . d= x+y x+y x + 1/x x +1 (b) We need to maximize the function d(x) found in (a), so we compute x2 + 1 − x · 2x 1 − x2 d0 (x) = . (x2 + 1)2 (x2 + 1)2 1 This is 0 when x = 1, positive when 0 < x < 1, and negative when x > 1 (remember that x is the sidelength of a triangle, so it must be positive). Hence d(x) is maximized when x = 1, and its maximal value is d(1) = 1/2. 4. The function is defined for all x 6= −1. We have lim − x→±∞ 1 = 0, x+1 lim − x→−1− 1 = ∞, x+1 lim − x→−1+ 1 = −∞, x+1 so that lim y = e0 = 1, x→±∞ lim y = ∞, x→−1− lim y = 0. x→−1+ Thus there is a horizontal asymptote y = 1 and a vertical asymptote x = −1. Next, we compute 1 y 0 = e−1/(x+1) · > 0 for all x, (x + 1)2 hence y is increasing on each of the intervals (−∞, −1) and (−1, ∞). There are no local maxima or minima (note that y approaches 0 as x → −1+ , but does not actually reach it.) Finally, y 00 = e−1/(x+1) · 1 −2 −2x − 1 −1/(x+1) + e−1/(x+1) · = e . 4 3 (x + 1) (x + 1) (x + 1)4 This is 0 when x = −1/2, positive when x < −1/2, and negative when x > −1/2. Thus y is concave up on (−∞, −1) and (−1, −1/2), concave down on (−1/2, ∞), and has an inflection point at (−1/2, e−2 ). The graph is below. 2